Does illness experience influence the recall of medical information?. Issue 6 (1st December 1998) - Krishnan, B; Glazebrook, C; Smyth, A
Abstract : Recall of a storyboard description of an unfamiliar illness was assessed in 66 healthy children and 40 children with chronic illness (cystic fibrosis or asthma). A significant interaction between verbal intelligence quotient and illness experience (p < 0.001) suggested that more able sick children may be resistant to learning new medical information.